Differential gene expression of bone marrow CD34+ cells in early and advanced myelodysplastic syndrome - Vasikova, A; Budinska, E; Belickova, M; Cermak, J; Bruchova, H (Neoplasma, 2009)
Myelodysplastic syndrome (MDS) is a hematopoietic stem cell disorder characterized by ineffective hematopoiesis and dysplasia in one or more blood cell lines. Because it often progress to poor outcome stages or acute leukemia we searched for candidate genes associated with disease progression. Using microarrays we performed gene expression profiling in CD34+ cells of 4 early and 4 advanced MDS patients and identified 286 significantly differentially expressed genes between these two categories. Out of these, 136 genes were up-regulated and 150 down-regulated in early MDS compared to advanced MDS. Using clustering analysis those two patient categories were clearly differentiated. Further, we selected three genes (ADAM8, BIRC5, MPL) for gene expression validation by qRT-PCR in an additional set of 29 MDS and sAML patients. We confirmed decreasing trend for BIRC5 expression from early to advanced stages of MDS, with the lowest levels in sAML patients. On the contrary, higher ADAM8 and MPL expression was observed in most advanced MDS patients compared to the early MDS patients. Association between gene expression levels and bone marrow blast proportion was tested, but only BIRC5 expression showed negative correlation (r=-0.83 at p<0.001). This study demonstrates stage-specific expression of some genes that may have potential prognostic significance.
Keywords: RNA, Messenger; Male; antigeny CD34; Myelodysplastic Syndromes; prognóza; buňky kostní dřeně; Neoplasm Staging; Adult; Aged; dospělí; mužské pohlaví; senioři; lidé středního věku; polymerázová řetězová reakce s reverzní transkripcí; stanovení celkové genové exprese; Oligonucleotide Array Sequence Analysis; Antigens, CD34; Gene Expression Profiling; myelodysplastické syndromy; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; Reverse Transcriptase Polymerase Chain Reaction; Prognosis; Female; Bone Marrow Cells; messenger RNA; staging nádorů; nádorové biomarkery; Middle Aged